Prolonged vertigo and ataxia after mandibular nerve block for treatment of trigeminal neuralgia - Arvind Chaturvedi; H H Dash (Wolters Kluwer Medknow Publications, 2011)
Common complications of neurolytic mandibular nerve block are hypoesthesia, dysesthesia, and chemical neuritis. We report a rare complication, prolonged severe vertigo and ataxia, after neurolytic mandibular blockade in a patient suffering from trigeminal neuralgia. Coronoid approach was used for right sided mandibular block. After successful test injection with local anesthetic, absolute alcohol was given for neurolytic block. Immediately after alcohol injection, patient developed nausea and vomiting along with severe vertigo, ataxia and hypertension. Neurological evaluation was normal except for the presence of vertigo and ataxia. Computerised tomography scan brain was also normal. Patient was admitted for observation and symptomatic treatment was given. Vertigo and ataxia gradually improved over 24 hours.